SELECTED INDICATORS OF THE GENDER PAY GAP IN THE EU AND ITS RELATIONSHIP WITH LABOUR FORCE PARTICIPATION RATE OF WOMEN (Research Bulletins of the Faculty of Economic Sciences, 2024)
The paper explores the causal relationship between the Gender Pay Gap and the Labour Force Participation Rate of women in the EU. Having outlined the nature and role of remuneration in the economy, it analyses the causes for both phenomena through the scope of various schools of economic thought, as well as uses recent empirical evidence and data to offer possible determinants for both the GPG and female LFPR, stemming from the social structure as well as legislation. Further, it uses regression analysis of historical data to find a negative relationship between the Gender Pay Gap and female Labour Force Participation Rate and discusses the limitations of the findings using the model. Lastly, using the above findings and previous legislation it offers policy solutions for states and private entities towards narrowing the pay and LFPR gaps, per the author’s opinion.
Keywords: gender pay gap, labour force participation gap, European Union